2021
DOI: 10.1038/s41467-021-21408-9
|View full text |Cite
|
Sign up to set email alerts
|

Lysates of Methylococcus capsulatus Bath induce a lean-like microbiota, intestinal FoxP3+RORγt+IL-17+ Tregs and improve metabolism

Abstract: Interactions between host and gut microbial communities are modulated by diets and play pivotal roles in immunological homeostasis and health. We show that exchanging the protein source in a high fat, high sugar, westernized diet from casein to whole-cell lysates of the non-commensal bacterium Methylococcus capsulatus Bath is sufficient to reverse western diet-induced changes in the gut microbiota to a state resembling that of lean, low fat diet-fed mice, both under mild thermal stress (T22 °C) and at thermone… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 73 publications
1
25
0
Order By: Relevance
“…Here, Th17/Tregs ratio was reversed, yet Tregs decreased upon SR1001 treatment. We speculated that this result was caused by SR1001 administration because of the complexity of Tregs 32 . Effects of SR1001 on Tregs and the complicated interrelationship between RORγt and Tregs require more investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Here, Th17/Tregs ratio was reversed, yet Tregs decreased upon SR1001 treatment. We speculated that this result was caused by SR1001 administration because of the complexity of Tregs 32 . Effects of SR1001 on Tregs and the complicated interrelationship between RORγt and Tregs require more investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Fresh feces were collected at baseline prior to EtOH feeding as well as at the termination of the study, and DNA was extracted using the NucleoSpin 96 soil kit (Macherey-Nagel, Düren, Germany) following the manufacturer's instructions. Baseline samples were processed as previously described (Jensen et al, 2021). Briefly, 30 ng DNA and 16S rRNA fusion primers were added for PCR followed by purification with Agencourt AMPure XP beads (Beckman Coulter, Indianapolis, IN).…”
Section: Fecal Microbiota Composition Analysis and Bioinformaticsmentioning
confidence: 99%
“…To determine the potential mechanisms underlying the beneficial effects of hBD-2 on EtOH-associated liver injury, we first analyzed the immunomodulatory effects of hBD-2, specifically focusing on well-known cytokines that play an important role in ALD pathogenesis and innate immunity. We measured the expression of liver and small intestine IL-22, a hepatoprotective cytokine which also exerts beneficial effects in the gut (Wang et al, 2014), and IL-17A, a cytokine with pleiotropic effects including gut microbial defense (Hong et al, 2017;Jensen et al, 2021). In Cohort 1, liver and intestinal IL-22 and IL-17A protein levels were unchanged following either EtOH feeding or hBD-2 administration (Figures 4A,B).…”
Section: Human Beta Defensin 2 Led To Favorable Immunomodulatory Changes In a Cohort-dependent Mannermentioning
confidence: 99%
“…Although the mechanisms involved in postbiotics bioactivity have not been fully understood, studies have reported various functions of postbiotics, including anti-inflammatory, antihypertensive and antioxidant activity [ 86 , 87 , 88 ]. For example, Benjamin at al found that whole-cell lysates of the non-commensal bacterium Methylococcus capsulatus Bath could improve glucose regulation, diminish hepatic immune infiltration, and change the gut microbiome composition in diet-induced obese mice [ 89 ]. Several properties of postbiotics, including their clear chemical structures, stability, and safety dose parameters grant them the potential to become the new generation of health products [ 90 , 91 ].…”
Section: Microorganisms From Other Origins and Kingdoms Beyond Fecal mentioning
confidence: 99%